Design, construction and utilization of a university plasma laboratory. (June 2020) - Gekelman, W.; Pribyl, P.; Lucky, Z.; Tang, S. W.; Han, J.; Qian, Y.
Abstract : We present the elements required to construct two devices used in an undergraduate plasma physics laboratory. The materials and construction costs of the sources, the vacuum systems and probe drives and electrical circuits are presented in detail in the text and the first appendix. We also provide the software for probe motion and data acquisition as well as the electrical schematics for key components. Experiments which have been performed are listed and two (resonance cones and whistler waves) are described in greater detail. The machines are flexible and original research is possible.